Asylum-Seeker and Refugee Protection in Sub-Saharan Africa: The Peregrination of a Persecuted Human Being in Search of a Safe Haven - Stone, Lee (Southern African Public Law, 2017)
Asylum-Seeker and Refugee Protection in Sub-Saharan Africa: The Peregrination of a Persecuted Human Being in Search of a Safe Haven by Dr Cristiano d’Orsi (Routledge Research in Asylum, Migration and Refugee Law, 2016)